Modulating the Microenvironments of Robust Metal Hydrogen‐Bonded Organic Frameworks for Boosting Photocatalytic Hydrogen Evolution - Lu, Chong‐Jiu; Shi, Wen‐Jie; Gong, Yun‐Nan; Zhang, Ji‐Hong; Wang, Yu‐Chen; Mei, Jian‐Hua; Ge, Zhao‐Ming; Lu, Tong‐Bu; Zhong, Di‐Chang (Angewandte Chemie International Edition, 2024)
Hydrogen‐bonded organic frameworks (HOFs) are outstanding candidates for photocatalytic hydrogen evolution. However, most of reported HOFs suffer from poor stability and photocatalytic activity in the absence of Pt cocatalyst. Herein, a series of metal HOFs (Co2‐HOF‐X, X=COOMe, Br, tBu and OMe) have been rationally constructed based on dinuclear cobalt complexes, which exhibit exceptional stability in the presence of strong acid (12 M HCl) and strong base (5 M NaOH) for at least 10 days. More impressively, by varying the ‐X groups of the dinuclear cobalt complexes, the microenvironment of Co2‐HOF‐X can be modulated, giving rise to obviously different photocatalytic H2 production rates, following the −X group sequence of −COOMe>−Br>−tBu>−OMe. The optimized Co2‐HOF‐COOMe shows H2 generation rate up to 12.8 mmol g−1 h−1 in the absence of any additional noble‐metal photosensitizers and cocatalysts, which is superior to most reported Pt‐assisted photocatalytic systems. Experiments and theoretical calculations reveal that the −X groups grafted on Co2‐HOF‐X possess different electron‐withdrawing ability, thus regulating the electronic structures of Co catalytic centres and proton activation barrier for H2 production, and leading to the distinctly different photocatalytic activity. Four robust metal hydrogen‐bonded organic frameworks with different electron‐withdrawing ability of functional groups have been successfully constructed, which exhibit distinctly different photocatalytic activity for hydrogen evolution, for the first time, highlighting the microenvironment modulation in HOFs plays an important role in regulating photocatalysis.